Leader Peptide‐Free In Vitro Reconstitution of Microviridin Biosynthesis Enables Design of Synthetic Protease‐Targeted Libraries. Issue 32 (23rd June 2016) - Reyna‐González, Emmanuel; Schmid, Bianca; Petras, Daniel; Süssmuth, Roderich D.; Dittmann, Elke
Abstract: Microviridins are a family of ribosomally synthesized and post‐translationally modified peptides with a highly unusual architecture featuring non‐canonical lactone as well as lactam rings. Individual variants specifically inhibit different types of serine proteases. Here we have established an efficient in vitro reconstitution approach based on two ATP‐grasp ligases that were constitutively activated using covalently attached leader peptides and a GNAT‐type N ‐acetyltransferase. The method facilitates the efficient in vitro one‐pot transformation of microviridin core peptides to mature microviridins. The engineering potential of the chemo‐enzymatic technology was demonstrated for two synthetic peptide libraries that were used to screen and optimize microviridin variants targeting the serine proteases trypsin and subtilisin. Successive analysis of intermediates revealed distinct structure–activity relationships for respective target proteases. Abstract : Natural products : A chemo‐enzymatic one‐pot synthesis approach was developed for tricyclic microviridins comprising lactone as well as lactam rings. The method was used to design and screen protease‐targeted libraries derived from short synthetic oligopeptides.